Entry into and Completion of Vocational Baccalaureate School in Switzerland: Do Differences in Regional Admission Regulations Matter? - Miriam Hänni; Irene Kriesi; Jörg Neumann (MDPI AG, 2022)
Upper secondary education in Switzerland is divided into a general and a vocational path. Approximately two thirds of adolescents attend the vocational path. The initial vocational education and training (IVET) can be combined with a federal vocational baccalaureate (FVB), which enables graduates to enter universities of applied sciences. The proportion of FVB holders varies considerably between Swiss regions. We study how admission regulations affect regional entry and graduation rates and how they interact with individual characteristics. We use longitudinal register data from the Federal Statistical Office to study individuals' chances of pursuing and obtaining a vocational baccalaureate in combination with data about cantonal admission criteria to vocational baccalaureate schools. We find that higher admission barriers reduce individuals' chances of pursuing a vocational baccalaureate, particularly among apprentices with low socio-economic status and those who pursue an FVB after their VET diploma. Against our expectations, high admission barriers are associated not only with lower entry rates but also with lower graduation rates.